Territorio, ambiente y actores : Aportes metodológicos para la formulación de Códigos urbanos. Caso Paraná, Entre Ríos. Área de la Bajada - Blanca, María Liliana (2012)
The proposed theme links the planning and regulation of land and its correlation with tools and methods of intervention and urban management, raised from an environmental vision. The object of study is the geographical area called here “The Área de La Bajada", in Parana Entre Rios. Area on which it is performed a comprehensive and conceptual approach to the territory based on Stlocus and Territorii methods and possible mechanisms of territorial management. Thus, from the categorical concepts of territory, actors and environment, it is proposed to provide both methodologies for understanding, explanation, analysis of the territory and places, and management tools to regulations based on territorial intelligence. From these notions then, is to perform a conceptual and policy linkages for the sustainable management of the territory that proposes to resolve the differences between the static policy and socio-spatial dynamics. During this analysis, it was included participatory mechanisms, such as workshops and surveys that contribute to the understanding of the actual, thought, legal, lived and future territory like a way to colaborate with process of reading and understanding of the place. Likewise, Stlocus assembly with Territorii, allows to investigate and analyze the place, from the recognition of patterns of occupation of the site, land ownership and vocations. Concepts that would be able to incorporate in regulations, categories and dimensions of urban development - land. Referred to the environmental, it isconsidered appropriate to develop the risk (vulnerability + threats), as an operational concept to fulfilment of two objectives: inclusion of actors to the dynamics of management and operationalization of environmental actions all over the territory. Afterwords, the methods chosen during the analizing process allow to arrived to three fundamentalconclusive issues: the proposed methods shall be flexibly applied to contribute to the understanding of the territory from the categorical concepts of space; social actors can be included in this inquiry at any stage of the process; participation and sustainable management of a territory as conditions needed in order to initiate a governance process to play down distorting market impacts, through the actions of a promoter and regulator State. State making distributive an inclusive policies and actions, to reduce the different interactions and dynamics between regulatory bodies and their direct link with the future desired territory by the citizens. In other words a a regulation system expressed through a new territorial intelligence.